How can ethnicity promote recognition of an ethnic identity? (International Seven Journal of Multidisciplinary, 2024)
The aim of this article is to find out and reflect on what has been produced in the last decade and a half of this century on the subject of ethnicity, from 2001 to 2016. The methodology adopted was a consultation of the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (CAPES) / MEC. The choice of topic was a personal decision, as it was a production for the end of a course with Professor Dr. Estevão Rafael Fernandes, who gave us autonomy to choose the topic. When I accessed the portal, I chose to search by subject. Entering the word ethnicity, the portal retrieved and made available 166 articles related to the topic, written in English and Spanish, of which 101 were peer-reviewed. I only chose articles written in Portuguese. As a selection criterion, I chose the most accessed articles on this topic. After refinement, the result was reduced to 10 articles. These are the articles on which this work is based.